Reduction of Fe Levels in Groundwater Using Aeration-Filtration Method with Tray Aerator System - Sari, Yelfira (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2021)
The presence of high iron (Fe) content in water consumption is a major factor that causes health and aesthetic problems. Its amount in water samples can be reduced by combining the aeration and filtration methods of water treatment. The aeration method basically involves making direct contact between air and water, which is usually done by adding both together. Subsequently, the filtration method uses porous media like sand, gravel, and activated charcoal to filter water.This research compares the effectiveness of aeration, filtration, and combined aeration-filtration methods of water treatment. For the aeration method, a form of trays aerator arranged in 6 levels with a distance of 20cm is used along with a varied contact time duration of 1, 3, and 5 hours. In addition, quartz sand, activated carbon, palm fiber, and coral were used as the media for the filtration method. The results obtained as the % value of iron (Fe) removal were varied at a contact time of 1, 3, and 5 hours for both the aeration and combined aeration-filtration method, and 46.95; 78.2; 82.48; 72.32; 81.71; 87.24; and 70.44 for the filtration method shows the working effectiveness of the tools. The combination of aeration with filtration provides maximum results when compared to using aeration alone or filtration methods alone.